Kit Carson (Washington, D.C.)
The famous scout Kit Carson in his last photograph taken in 1868 by the noted Civil War photographer Bundy. The photo was taken in Washington, DC when Carson was there with a group of Indians to negotiate a treaty.
Black and White photographs
Master list item #: 21
File location is in the Raton file Cabinet
Keywords: Carson, Kit; Bundy; Male Photographs; Civil War Photographers; Portrait Photographs; Taos, New Mexico; Washington, DC